Using 3-cell chaotic map for image encryption based on biological operations - Saberikamarposhti, Morteza (Springer, 2014)
Recently, image encryption has emerged as an extremely urgent need to provide high protection for secure images against being used without any authorization. In the present paper, the 3-cell chaotic map known as cycling chaos was employed for image encryption based on biological operations. In order to increase security of the proposed method, the 120-bits secret key is used. DNA Sequences and cycling chaos were used to scramble the positions of the image pixels, and then the pixels grey values were modified using a mask DNA generated by cycling chaos. The obtained results demonstrated high security of the proposed method, and it was found acceptably resistant against different well-known attacks.